Analisis Kuat Lentur Beton SCC Menggunakan Fiberglass Dengan Variasi Additive Sika Viscocrete - Hamdan Hamdan; Adnan Adnan; Abd. Muis B (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Self Compacting Concrete (SCC) is an innovative concrete that can compact itself (without vibrators) and flow under its own weight to saturate the shape without segregation. The SCC material is not much different from ordinary concrete, namely coarse aggregate, fine aggregate, cement, water, only SCC has additional ingredients such as superplasticizer. This research uses quantitative methods. The aim of this research is to determine the workability, compressive strength, flexural strength of SCC concrete with the addition of 2% fiberglass to each sample with added material in the form of sika visconcrete with variations of 0%, 1%, 1.5%, and 2%, % of the cement weight. Slump flow testing was carried out which was obtained from several variations of SV `0%, 1%, 1.5%, 2%, the slump flow values were obtained for 80 mm fiber concrete and 550 mm, 575 mm, 600 mm SCC concrete with the time taken to reach 500 mm of 4.25 seconds, 3.57 seconds and 2.11 for SCC concrete. The compressive strength value of the cylinder size (15 x 30) in samples BFS0, BFS1, BFS2BFS3 aged 28 days obtained a compressive strength of 30.29 Mpa, 34.44 Mpa, 31.23 Mpa, while the flexural strength test of the beam was 15 x 15 x 60 d samples BFS0, BFS1, BFS2BFS3 obtained results of 3.11 Mpa, 4.35 Mpa, 3.64 Mpa and 3.29 Mpa, excessive use of visconcrete in the concrete mixture can reduce the strength of the samples.